A documentary study of natural resources and ways of protecting them - محمدعلي, د.ندى خليفة; عبدالوهاب, اريج محي (Journal of Planner and Development, 2010)
The problem of research is that there are ways to protect and sustain environmentally important sites in Iraq. There are no documentary sources for these sites, such as the natural landscape of natural and important natural resources, which suffer from severe environmental neglect